OPHTHALMIC PROFILE OF CHILDREN BORN PRE-TERM - de Freitas Machado, Ana Caroline; Castro Verçosa, Islane Maria (Cadernos ESP, 2021)
Objective: To report ophthalmological findings of premature children. Methods: Observational, descriptive, retrospective and cross-sectional study of premature children born at the Hospital Geral de Fortaleza and attended at the ophthalmopediatrics clinic of this service from July to December 2017. Results: 30 children aged 4 to 18 months were evaluated, with gestational age of birth between 26 and 36weeks and 6 days. Twenty-one children (66.7%) had an appropriate ophthalmologic evaluation for their age. Strabismus was the main eye disorder, found in 5 (16.67%) children. The most common refractive error was hyperopia and astigmatism. Conclusion: Most of the children evaluated had an eye examination suitable for their age. Further studies are needed to validate the hypothesis that prematurity alone is not a risk factor for ophthalmic diseases. It is necessary to raise awareness about the importance of the first complete eye evaluation between 6 months and 1 year of life for children.